Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.7554/elife.81856
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing CRISPRi efficacy and accessibility with dual-sgRNA libraries and optimal effectors

Abstract: CRISPR interference (CRISPRi) enables programmable, reversible, and titratable repression of gene expression (knockdown) in mammalian cells. Initial CRISPRi-mediated genetic screens have showcased the potential to address basic questions in cell biology, genetics, and biotechnology, but wider deployment of CRISPRi screening has been constrained by the large size of single guide RNA (sgRNA) libraries and challenges in generating cell models with consistent CRISPRi-mediated knockdown. Here, we present next-gener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 76 publications
1
47
0
Order By: Relevance
“…For this purpose, we used the MeWo melanoma cell line, which is also significantly enriched for a T2 melanocyte transcriptional signature (Normalized enrichment score = 1.25, adjusted p-value = 0.0018). We used a previously established CRISPR interference (CRISPRi) system 42 for targeted gene knockdowns, employing a pool of guide RNAs (gRNAs) targeting the 100 genes that make up the T2 signature, as well as the 100 T1 genes as a control set. We transduced MeWo cells that constitutively express dCas9-KRAB and luciferase with the gRNA-expressing lentiviruses in a pooled fashion and injected them into the tail veins of NSG (NOD scid gamma) mice for lung colonization assays.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, we used the MeWo melanoma cell line, which is also significantly enriched for a T2 melanocyte transcriptional signature (Normalized enrichment score = 1.25, adjusted p-value = 0.0018). We used a previously established CRISPR interference (CRISPRi) system 42 for targeted gene knockdowns, employing a pool of guide RNAs (gRNAs) targeting the 100 genes that make up the T2 signature, as well as the 100 T1 genes as a control set. We transduced MeWo cells that constitutively express dCas9-KRAB and luciferase with the gRNA-expressing lentiviruses in a pooled fashion and injected them into the tail veins of NSG (NOD scid gamma) mice for lung colonization assays.…”
Section: Resultsmentioning
confidence: 99%
“…A dCas9-KRAB-mCherry lentiviral construct (pHR-UCOE-EF1A-dCas9-HA-2xNLS-XTEN80-KRAB-P2A-mCherry) 42 was used to generate CRISPRi-competent MeWo and A375 cells. HEK293T cells were maintained in DMEM supplemented with 10% FBS, penicillin, streptomycin and amphotericin B, and passaged using 0.05% Trypsin prior to cells reaching 90% confluency.…”
Section: Generation Of Mewo and A375 Crispri Linesmentioning
confidence: 99%
“…201 Large-scale CRISPRi screening was successfully performed using Zim3-dCas9 and dual sgRNA libraries. 202 The study identified AARS, DNAJC19, and POLR1D in K562 leukemia cells. Screening for altered CREs in acute leukemia followed by CRISPR/dCas9-p300 or CRISPR/dCas9-KRAB identified oncogenic and tumor-suppressive CREs.…”
Section: Epigenome Editing In Cancer Research and Sarcoma Researchmentioning
confidence: 93%
“…The screening of CREs at the ARID5B locus identified variants that affect transcription factor binding; in addition, heritable acute lymphoblastic leukemia risk variants were identified 201 . Large‐scale CRISPRi screening was successfully performed using Zim3‐dCas9 and dual sgRNA libraries 202 . The study identified AARS, DNAJC19 , and POLR1D in K562 leukemia cells.…”
Section: Crispr/dcas9‐mediated Epigenome Editingmentioning
confidence: 99%
“…1A). Following tumor establishment, lentiviral dual-sgRNA libraries 15 targeting 48 genes that were nominated from in vitro CRISPRi growth or radiation modifier screens (Supplementary Fig. 1 and Supplementary Table 1) plus non-targeting sgRNA controls were delivered to intracranial tumors using CED.…”
Section: Mainmentioning
confidence: 99%